Pelatihan Pengenalan Penggunaan Mesin 3d Printing Di Universitas Pahlawan Tuanku Tambusai - Syifa Tanjung, Lailatul; Azriadi, Emon; Fiatno, Aris; Kumala Sari, Resy (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
Students are one of the factors that become a social vehicle for the development of the younger generation in society. This is because in college students get a lot of experience and knowledge that can be applied in society. Students can also be considered as a social platform for the development of young people who grow and develop on the basis of social awareness and responsibility from, by and for the community, especially the younger generation in the territory of an area or traditional community on an equal footing and develop in the field of social welfare business and other related fields. oriented towards improving social welfare. As stated in the definition, students are expected to be able to overcome various social welfare problems faced by the younger generation and be able to develop the potential of the younger generation in their environment and will have a positive impact on society. There are many activities that can be carried out that involve students in society related to social, spiritual, and sports. However, there are still not many activities that can hone skills and can increase motivation to become a creative generation and work independently. Therefore, researchers took the initiative to conduct 3D printing training for students to improve their skills and productivity in producing works that are economically valuable.